Superstructure Stabilization of Ballast Bedded Railway Tracks with Geogrids (Hungarian Journal of Industry and Chemistry, 2011)
The paper deals with the research and development of the authors related to investigation of geogrid railway ballast reinforcement. It summarizes the theory of the geometrical deterioration of railway tracks, as well as the advantages of the use of geogrid reinforced ballast in railway superstructure. This article summarizes the results of the field tests with five different geogrid types on a Hungarian main railway line and laboratory multi-level shear box tests. It points out to future research possibilities, for example the modelling of laboratory multi-level shear box tests with discrete element method that may certify their results.